Gradual implementation of first trimester screening in a population with a prior screening strategy: population based cohort study - Calda, Pavel; Sípek, Antonín; Gregor, Vladimír (Acta obstetricia et gynecologica Scandinavica, 2010)
OBJECTIVE: To evaluate the implementation of first trimester screening in the Czech Republic during 1996-2007 on the number of infants born with numerical chromosomal anomalies, the gestational age at diagnosis and the number of invasive procedures. DESIGN: A population based cohort study. SETTING: National Registry of Congenital Anomalies, 53 Czech Republic Genetic Departments. POPULATION: About 100,000 pregnancies per year. MAIN OUTCOME MEASURES: Primary outcomes were the rates of fetuses and newborns with diagnosed numerical chromosomal anomalies and the gestational age at diagnosis. Secondary outcomes were the rates of chorion villus sampling (CVS) and amniocenteses and the contribution of age groups on the detection rate of trisomy 21. RESULTS: The number of newborns with Down's syndrome decreased from 5.42/10,000 in 1996 to 3.66/10,000 newborns in the 2007. The total incidence of Down's syndrome increased from 13.42 to 20.66/10,000. The detection rate in women <35 years increased from 35.59 in 1996 to 45.08 in 2007; in women >35 years from 23.73 to 38.52. The number of amniocenteses/detected case of Down's syndrome was 124 in 1996 and 123 in 2007. The corresponding number of CVS decreased dramatically from 83 in 1996 to 10 in 2007. CONCLUSIONS: Despite the increase of maternal age and the corresponding increase of Down's syndrome, the number of newborns with Down's syndrome decreased. Implementation of the first trimester combined screening leads to a shift towards earlier diagnosis of all major chromosomal abnormalities.
Keywords: první trimestr těhotenství; Maternal Age; kohortové studie; Chorionic Villi Sampling; prenatální diagnóza; Cohort Studies; gestační stáří; Česká republika; Gestational Age; Pregnancy; těhotenství; Adult; odběr choriových klků; dospělí; Down Syndrome; amniocentéza; incidence; registrace; Prenatal Diagnosis; Czech Republic; novorozenec; lidé; ženské pohlaví; Humans; věk matky; Infant, Newborn; Amniocentesis; Registries; Downův syndrom; Female; Pregnancy Trimester, First; Incidence